Exploring of cellulose nanocrystals from lignocellulosic sources as a powerful adsorbent for wastewater remediation - Norfarhana, A. S.; Khoo, P. S.; Ilyas, R. A.; Ab Hamid, N. H.; Aisyah, H. A.; Norrrahim, Mohd Nor Faiz; Knight, V. F.; Rani, M. S. A.; Septevani, Athanasia Amanda; Syafri, Edi; Annamalai, Pratheep K. (Springer, 2024)
The increasing global concern over the contamination of natural resources, especially freshwater, has intensified the need for effective water treatment methods. This article focuses on the utilization of Cellulose nanocrystals (CNCs), sourced from lignocellulosic materials, for addressing environmental challenges. CNCs a product of cellulose-rich sources has emerged as a versatile and eco-friendly solution. CNCs boast unique chemical and physical properties that render them highly suitable for water remediation. Their nanoscale size, excellent biocompatibility, and recyclability make them stand out. Moreover, CNCs possess a substantial surface area and can be modified with functional groups to enhance their adsorption capabilities. Consequently, CNCs exhibit remarkable efficiency in removing a wide array of pollutants from wastewater, including heavy metals, pesticides, dyes, pharmaceuticals, organic micropollutants, oils, and organic solvents. This review delves into the adsorption mechanisms, surface modifications, and factors influencing CNCs’ adsorption capacities. It also highlights the impressive adsorption efficiencies of CNC-based adsorbents across diverse pollutant types. Employing CNCs in water remediation offers a promising, eco-friendly solution, as they can undergo treatment without producing toxic intermediates. As research and development in this field progress, CNC-based adsorbents are expected to become even more effective and find expanded applications in combating water pollution.